Ensuring Healthcare Efficiency in the Context of the Medical and Pharmaceutical Staff Regulation - Guzal G. Galiakbarova; Yenlik N. Nurgaliyeva; Elmira B. Omarova; Svetlana B. Zharkenova; Muslim K. Khassenov (Emerging Science Journal, 2022)
This article aims to substantiate the impact of socio-economic labor protection for healthcare professionals based on developing legislative regulations in some OECD and EAEU countries and identifying their relationship with the efficiency of healthcare systems. The methodology includes general scientific methods (systemic analysis, synthesis, comparison, abstraction, induction, deduction, and modeling) and special research methods (formal logical, structural, and functional). The results of international rankings evaluating healthcare systems were used to determine the list of states for comparative legal analysis. Also, empirical methods were used: meetings, questionnaire surveys, and interviews held in 2021 with medical and pharmaceutical workers in Kazakhstan. The research results showed that states with special labor regulations for medical and pharmaceutical personnel occupy stable leading positions in international rankings regarding healthcare evaluation. On the other hand, based on the example of the EAEU countries with an insufficient level of specialization in labor regulation for these categories of workers, some states occupy weak positions in similar international ratings. This paper is novel because previously, there was no debate in the literature justifying the finding that specifics in the labor regulation of medical and pharmaceutical staff, along with other factors, influence the healthcare system's efficiency and development. Doi: 10.28991/ESJ-2022-06-06-05 Full Text: PDF